The inter-connections of ∑ 3 boundaries in pure iron. (February 2017) - Wang, Weiguo; Chen, Song; Rohrer, Gregory S; Chen, Wenzhe
Abstract: An integrated method involving electron backscatter diffraction, five-parameter analysis and crystallographic analysis, was employed to determine the inter-connections of ∑ 3 boundaries in a cold rolled and annealed pure iron. Three types of inter-connections were observed, including 1 1 2/1 1 2, 1 1 1/1 1 5 and 0 1 1/0 1 1 which are present in the samples annealed for 15, 30 and 45 min at 620 °C after cold rolling, respectively. The results indicate though 1 1 2/1 1 2 is considered as low energy inter-connection in pure iron, it is replaced by 0 1 1/0 1 1 during annealing. Graphical abstract: